1971
DOI: 10.1104/pp.47.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Potential Differences in Cells of Barley Roots and Their Relation to Ion Uptake

Abstract: Single cell electropotentials of barley (Hordeum vulgare L., cv. 'Compana') root cortex were measured at different external concentrations of KCl in the presence of Ca2+. The roots were low in salt from seedlings grown on 0.5 mM aerated CaSO4 solution. Thus, the conditions were equivalent to those used to define the dual nmechanisms found with radioactive tracer-labeled ion uptake. In 0.5 mM CaSO4 alone, there is an increase with time of cell negativity from about -65 millivolts 13 minutes after cutting segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…8B). In a similar study of barley root AI) values, Pitman et al (1971a) observed depolarizations of 43, 28, and 53 mV per decade of [K+], between 1 and 2.5, 2.5 to 10, and 10 to 25 mM [K+],, respectively. Furthermore, our measurements of AI) in Chlamydomonas by the use of TPP+ revealed that AI) was hyperpolarized as externa1 pH increased (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…8B). In a similar study of barley root AI) values, Pitman et al (1971a) observed depolarizations of 43, 28, and 53 mV per decade of [K+], between 1 and 2.5, 2.5 to 10, and 10 to 25 mM [K+],, respectively. Furthermore, our measurements of AI) in Chlamydomonas by the use of TPP+ revealed that AI) was hyperpolarized as externa1 pH increased (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…There was no change in respiration rate during washing (just as for traygrown roots, Table I). and there was no correlation between respiration rates and phosphate absorption rates (Table VIII) (22). The fact that the cell potential starts rising immediately suggests that induction may be linked to this phenomenon.…”
Section: Resultsmentioning
confidence: 94%
“…2). Pitman et al (10) suggested that PD might rise with the removal of a source of hormone, sealing of plasmodesmata, or an increase in the salt concentration in the cytoplasm. We have no data for evaluating these possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…There is a growing belief that proton pumps are the source of the potential for active transport (3,12 (Fig. 4) (10), but in both the transformation is complete in 4 to 6 hr. We find the entire increase lies in the electrogenic PD, which levels out at the same time as the increase in phosphate absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation